2021
DOI: 10.1007/s11538-021-00910-7
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Epidemiological Models with Social Dynamics

Abstract: In this work we study a Susceptible-Infected-Susceptible model coupled with a continuous opinion dynamics model. We assume that each individual can take measures to reduce the probability of contagion, and the level of effort each agent applies can change due to social interactions. We propose simple rules to model the propagation of behaviors that modify the level of effort, and analyze their impact on the dynamics of the disease. We derive a two dimensional set of ordinary differential equations describing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In particular, it was shown that, for negative values of the parameter 𝛿, the resulting equilibrium contact distribution is given by a distribution with polynomial tails (17). On the other hand, slim tailed distributions can be obtained for positive values of 𝛿, see (15) and (16).…”
Section: Selective Control Of the Kinetic Epidemic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was shown that, for negative values of the parameter 𝛿, the resulting equilibrium contact distribution is given by a distribution with polynomial tails (17). On the other hand, slim tailed distributions can be obtained for positive values of 𝛿, see (15) and (16).…”
Section: Selective Control Of the Kinetic Epidemic Modelmentioning
confidence: 99%
“…Special attention was recently paid by the scientific community to the role and the estimate of the distribution of contacts between individuals as also a relevant cause of the potential pathogen transmission 11‐13 . Nevertheless, we have often limited information on the real social features of a population, whose characteristics are structurally uncertain and may frequently change due to exogenous processes that are also influenced by psychological factors, determining different responses in terms of individuals' protective behavior, see for example, References 14 and 15.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors and perspectives are likely involved in feedback loops between disease dynamics and prophylaxis. Many of these have been modeled, including, for instance, fear of infection mediated by messages from social circles or mass media [10][11][12][13], social influence [5, 14,15], socioeconomic utility maximization [16][17][18], and evolutionary game theory [19][20][21][22][23]. Modeling such factors helps in understanding the determinants of the prophylactic responses of human populations to disease risk and is crucial for pre-or post-assessment of the effectiveness of causal interventions, including non-pharmaceutical interventions such as mask wearing, social distancing, and hand washing.…”
Section: Introductionmentioning
confidence: 99%
“…Buonomo et al (2022) and the references therein. In this direction, we mention the recent results in Della Marca et al (2022b), Giambiagi Ferrari et al (2021), Kontorovsky et al (2022) and Zhou et al (2019) where agent-based dynamics are upscaled at the level of observable epidemiological quantities.…”
Section: Introductionmentioning
confidence: 99%